Analysis of the problem of prison overcrowding in Colombia (2022)
The purpose of this research is to explore how overcrowding has become a problem that really affects people deprived of their liberty. analyzing how effective public policy and its historical theoretical framework have been to determine its validity and application within prisons today, in addition to giving an exact overview of the causes of overcrowding in its multiple variables, showing the installed capacity, budget to solve the problem and how this has attracted the attention of society generating concerns in various social, cultural and economic sectors. Human rights violations are observed, due to the lack of basic and essential elements that the State must guarantee, where issues of food, health, dignity and programs for the resocialization of personnel deprived of liberty have failed, therefore, public prison policy has only focused on building more buildings to solve the problem, leaving aside many more factors that are not given proper priority or treatment. In addition, we analyze and statistically identify the levels of overcrowding in penitentiary centers The Modelo and The Picota In the time periods 2019 to 2021 and the emergence of COVID-19 Within the existing problem, this problem has generated enough debates, requests and declarations from national and international organizations due to the worrying situation.